Analisis Sistem Eksitasi Pada Generator Sinkron 11KV Unit 2 ULPLTA Sipansihaporas - Gaul Pernandes Tambunan; Helfridolin Gultom; Heber Riko Parulian Manalu; Desman Jonto Sinaga (JURNAL ILMIAH NUSANTARA, 2026)
The excitation system is a fundamental component in the operation of synchronous generators, functioning to regulate output voltage stability and control reactive power during dynamic load variations. This research was conducted at ULPLTA Sipansihaporas Unit 2, which generates 17 MW using a static excitation system equipped with an Automatic Voltage Regulator (AVR) and 110 V DC battery for initial excitation. The objective of this study is to analyze the excitation process, identify the main components of the excitation system, and evaluate its performance under operational load conditions. Data for this research was obtained directly from field observations and generator operational parameters recorded through the Central Control Room (CCR). The results indicate that the excitation current and voltage remain constant at 520 A and 58 V respectively despite fluctuations in active and reactive power. The system was able to maintain the terminal voltage at 11.4 kV and frequency at 50 Hz ± 0.1, demonstrating stable performance and operational reliability. These findings confirm that the excitation system of Unit 2 performs efficiently in supporting power system stability and reliability within the regional grid.